AB0014 Lack of Association between AB0, PPAP2B, ADAMST7, PIK3CG, EDNRA and Carotid Intima-Media Thickness, Carotid Plaques and Cardiovascular Disease in Patients with Rheumatoid Arthritis. (10th June 2014) - Lopez, R.; Genre, F.; García Bermudez, M.; Ubilla, B.; Castañeda, S.; Llorca, J.; González-Juanatey, C.; Corrales, A.; Miranda-Filloy, J.A.; Pina, T.; Gόmez-Vaquero, C.; Rodríguez-Rodríguez, L.; et al.
Abstract : Background: Rheumatoid arthritis (RA) is an autoimmune inflammatory disease associated with accelerated atherosclerosis and increased cardiovascular (CV) disease. A genetic component has been implicated in atherosclerosis. Recently, the ABO rs579459, PPAP2B rs17114036, ADAMTS7 rs3825807 polymorphisms have been associated with coronary artery disease [1] and the PIK3CG rs17398575, EDNRA rs1878406 variants with carotid plaques in general population [2]. Objectives: We aimed to determine the potential role of these 5 polymorphisms and cIMT, presence/absence of carotid plaques and CV events in RA. Methods: Polymorphisms were analyzed in 2140 Spanish RA patients by TaqMan assays. Subclinical aterosclerosis was determined by carotid ultrasonography (US) in 620 patients. Results: No statistical significant differences were observed when the ABO rs579459, PPAP2B rs17114036 and ADAMTS7 rs3825807 polymorphisms and CV events were compared. It was also the case when PIK3CG rs17398575 and EDNRA rs1878406 polymorphisms and cIMT and carotid plaques were analyzed. Conclusions: Our results do not confirm an association of these 5 polymorphisms and subclinical atherosclerosis and CV in RA. References: Schunkert H, et al. Nat Genet 2011;43:333-8. Bis JC, al. Nat Genet 2011;43:940-7. Acknowledgements: This study was supported by European Union FEDER funds and "Fondo de Investigaciόn Sanitaria" (PI06/0024, PS09/00748 and PI12/00060) from `Instituto de Salud Carlos III" (ISCIII, Spain). It was also partially supported by RETICS Programs RD12/0009/0013 and RD12/0009/0004 (RIER) from ISCIII and by grants from the European IMI BTCure Program. RLM is a recipient of a Sara Borrell postdoctoral fellowship from ISCIII (CD12/00425). FG and BU are supported by funds from the RETICS Program (RIER). MGB is a beneficiary of a grant from Fundaciόn Española de Reumatología (FER). Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1760